Cryopreservation of mature coconut embryos by desiccation method - Anitha Karun; K.K. Sajini; V.A. Parthasarathy (International Coconut Community Journal, 2005)
Mature embryos of West Coast Tall variety of coconut could be cryopreserved after desiccation pretreatments and retrieved into plantlets. The desiccation pretreatment and optimum duration for dehydration of zygotic embryos were standardized. The maximum retrieval of healthy plantlets was obtained from the embryos subjected to 18 hours silica gel or 24 hours laminar airflow desiccation pretreatment. Irreversible damage caused by desiccation to the death of the shoot meristem was noticed when the water content reduced to 20%.